Part 2. Mechanistic aspects of the reduction of S-alkyl-thionocarbonates in the presence of triethylborane and air - Allais, Florent; Boivin, Jean; Nguyen, Van Tai (Beilstein Journal of Organic Chemistry, 2007)
Experiments conducted with deuterated compounds demonstrated that during the reduction of S-alkylxanthates with triethylborane, the hydrogen atom transferred has several competing origins. Hydrogen abstraction from water (or an alcohol) is the most favourable route.